2021
DOI: 10.1002/nop2.935
|View full text |Cite
|
Sign up to set email alerts
|

The risk of venous thromboembolism associated with midline catheters compared with peripherally inserted central catheters: A systematic review and meta‐analysis

Abstract: Background: Both midline catheters (MCs) and peripherally inserted central catheters (PICCs) can cause venous thromboembolism (VTE), but the prevalence associated with each is controversial.Objective: To compare the risk of VTE between MCs and PICCs with a systematic review and meta-analysis. Methods:The Web of Science Core Collection, PubMed, Scopus, Embase, the Cochrane Library and ProQuest were searched from inception to January 2020. All studies comparing the risk of VTE between MCs and PICCs were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 35 publications
(56 reference statements)
0
9
1
Order By: Relevance
“…In a multicenter prospective study of 477 cancer patients who received a total of 50,841 catheterdays, 9 patients (1.9%) developed symptomatic upper extremity deep vein thrombosis (16). In another study, Lu et al included 86 studies for a meta-analysis and demonstrated that the incidence of PICC-related venous thrombosis was 2.29% (17). In another study by Jones et al, catheter-related deep vein thrombosis occurred in 5.5% of PICC patients (18).…”
Section: Discussionmentioning
confidence: 99%
“…In a multicenter prospective study of 477 cancer patients who received a total of 50,841 catheterdays, 9 patients (1.9%) developed symptomatic upper extremity deep vein thrombosis (16). In another study, Lu et al included 86 studies for a meta-analysis and demonstrated that the incidence of PICC-related venous thrombosis was 2.29% (17). In another study by Jones et al, catheter-related deep vein thrombosis occurred in 5.5% of PICC patients (18).…”
Section: Discussionmentioning
confidence: 99%
“…Categorization as minor and major provoking risk factors was based on the guidance provided by the International Society on Thrombosis and Haemostasis (ISTH) [ 36 ]. In addition to the ISTH-based criteria, the presence of an intravenous catheter [ 37 ] and May-Thurner syndrome (>70% iliofemoral compression) [ 38 ] were categorized as major risk factors, whereas immobilization > 4 h [ 39 ] and heavy smoking (>20 pack years) [ 40 ] as minor risk factors. VTE in the presence of merely an environmental risk factor (male sex and older age) was categorized as unprovoked thromboembolism.…”
Section: Methodsmentioning
confidence: 99%
“…Categorization as minor and major provoking risk factors of VTE was based on criteria provided by the International Society on Thrombosis and Haemostasis (ISTH) [30]. In addition to the ISTH based criteria, the presence of intravenous catheter [31] or May-Thurner syndrome (>70 % iliofemoral compression) [32] were categorized as major risk factors, whereas immobilization >4 h [33] and heavy smoking (>20 pack years) [34] as minor risk factors. VTE in the presence of merely an environmental risk factor (male sex and older age) was categorized as unprovoked thromboembolism.…”
Section: Methodsmentioning
confidence: 99%